An Intelligent Packet Loss Control Heuristic For Connectionless Real-Time Voice Communication - Şensoy, Murat; Yılmaz, Burcu; Yılmaz, Erdoğan (Hindawi Publishing Corporation, 410 Park Avenue, 15Th Floor, #287 Pmb, New York, Ny 10022 Usa, 2010)
Time critical nature of the real-time communication usually makes connection-oriented protocols such as TCP useless, because retransmission of old and probably expired packets is not desired. However, connectionless protocols such as UDP do not provide such packet loss control and suitable for real-time communication such as voice or video communication. In this paper, we present an adaptive approach for the intelligent packet loss control for connectionless real-time voice communication. Instead of detecting and resending lost voice packets, this heuristic estimates the packet loss rate adaptively using a modified version of reinforcement learning and resends the most critical packets before they are expired. Our simulations indicate that this approach is promising for a remarkable improvement in QoS of real-time voice communication.